Telomere length and telomerase activity in osteoporosis and osteoarthritis - Fragkiadaki, Persefoni (Exp Ther Med, 2020)
Osteoarthritis (OA) and osteoporosis (OP) are associated skeletal pathologies and have as a distinct feature the abnormal reconstruction of the subchondral bone. OA and OP have been characterized as age-related diseases and have been associated with telomere shortening and altered telomerase activity (TA). This review discusses the role of telomeres and telomerase in OA and OP pathologies and focuses on the usability of telomere length (TL) and the rate of telomere shortening as potential disease biomarkers. A number of studies have demonstrated that telomere shortening may contribute to OA and OP as an epigenetic factor. Therefore, it has been claimed that the measurement of TL of chondrocytes and/or peripheral blood cells may be an appropriate marker for the evaluation of the progression of these diseases. However, there is a need to be perform further studies with larger cohorts, with the aim of obtaining objective results and a better understanding of the association between TL, inflammation and aging, in order to provide further insight into the pathophysiology of degenerative joint diseases.